Practical and ethical challenges in co-producing technology for good in justice settings - Morris, Jason (Journal of criminology, 2024)
In this article, we reflect critically on the role of digital technology in supporting desistance from crime, and the process and outcomes of co-producing digital resources in that context. Drawing on concepts of social harm, and co-production (or “working-making-doing together”), we consider the risks of digital technology perpetuating coercive aspects of the justice system. We advocate for the conscientious inclusion of people with lived experience of criminalisation in the design, implementation, and evaluation of technology that supports desistance as one way of mitigating such risks. People’s lived experiences can attune them to underlying harms in the design and use of digital tools in the justice system and help safeguard future users of that technology. We also acknowledge the costs, risks, and complexities of this work. For instance, co-production may give permanence to voices and stories of lived experiences with both the power to inspire and promote desistance and the potential to reproduce or reinforce stigma and exclusion. We reflect on such ethical complexities by considering whose needs are served in co-producing technology to support desistance. We conclude by suggesting that the recruitment and promotion of experts by experience within justice organisations can help to create a learning culture where there is a heightened awareness of user experience and potential harms in the design, implementation, and evaluation of justice technology. Please note, this paper provides the authors’ reflections on co-producing technology that supports desistance. It is not intended to set out HMPPS policy on digital rehabilitative services or co-production methods. It is written in conversation with a colleague/interlocutor with lived experience of criminalisation and imprisonment, who remains anonymous here for various reasons and to whom the article is dedicated.